Global Financial Crises: Origin and Management - Koh, Hock Lye; Teh, Su Yean; Tan, Wai Kiat (International Journal of Economics and Financial Issues, 2016)
The world has witnessed a succession of three global financial crises in the past two decades. During each crisis, many financial institutions failed. Credit became either unavailable or too costly for business, as seen in the recent financial turmoil in Greece. Similar situation also prevailed during the 1997-1998 Asian Financial crisis, requiring the International Monetary Fund to rescue Indonesia, Korea and Thailand. A major cause of these crises is the high levels of sovereign and corporate debts. Central banks were prompted to intervene by the injections of large liquidity with low interest rates into the financial systems. Cheap liquidity often leads to high asset valuations, a root cause of another future crisis. Cheap liquidity also might lead to future high inflation and unsustainable sovereign and corporate debts. This paper begins with providing a qualitative-quantitative appraisal of these three recent financial crises, beginning with the 1997-1998 Asian Financial Crisis, through the 2008 US Great Recession, and the ongoing global recession. We argue that the 2008 US Great Recession was an inevitable consequence of the action of Asian countries in building sufficient foreign reserves in an attempt to insulate the country from future external shocks. The 2008 contagious crisis quickly spread to the EU zone and ultimately worldwide. The paper ends with some suggestions for managing future financial crisis, with particular reference to Asia that entails the formation of a pan-Asia economic grouping to resolve unending currency issues and other trade related problems, with China and Japan playing the leading role. Keywords: Financial Crisis Management; Sovereign Debts JEL Classifications: G1; G2; G3